Polyphenolic content, in vitro antioxidant activity and chemical composition of extract from Nephelium lappaceum L. (Mexican rambutan) husk - Hernández, Cristian; Ascacio Valdés, Juan; De la Garza, Heliodoro; Wong Paz, Jorge; Aguilar González, Cristóbal Noé; Martínez Ávila, Guillermo Cristian Guadalupe; Castro López, Cecilia; Aguilera Carbó, Antonio Francisco (2017)
Objective: To determinate the recovery of total polyphenolic compounds content, in vitro antioxidant activity and HPLC/ESI/MS characterization of extract from Nephelium lappaceum L. (Mexican rambutan). Methods: The rambutan husk extract was obtained by aqueous extraction and a polyphenolic fraction was recovered using Amberlite XAD-16. The total polyphenolic compounds content was determined by the Folin Ciocalteu and butanol-HCI methods. In vitro antioxidant activity was performed using ABTS and ferric reducing antioxidant power methods. Results: Mexican rambutan husk showed a total polyphenolic content of 582 mg/g and an evident antioxidant activity by ABTS and ferric reducing antioxidant power analysis. The HPLC/ESI/MS assay allowed the identification of 13 compounds, most of which belong to ellagitannins. Geraniin, corilagin and ellagic acid were present in the sample; the mineral composition was also evaluated. Conclusions: Rambutan husk cultivated in Mexico is a promising source for the recovery of added value bioactive compounds with antioxidant activity, which have potentialapplications as bioactive antioxidant agents for the treatment of diseases.